Application of Crumb Rubber Modified Bitumen in the Asphalt Concrete Mix - Neupane, Shila; Shahi, Thusitha Chandani (Journal on Transportation System and Engineering, 2025)
Nepal has significant potential for road development projects, which require substantial financial resources for construction, maintenance, and operation over time. Bitumen is widely used to construct durable road pavements. However, increasing vehicles and deteriorating road conditions necessitate effective pavement management. The rise in vehicles also leads to a gradual increase in waste tyres, which, along with other carbon-based products, contribute to environmental pollution. The durability and quality of road pavements depend heavily on the type and properties of bitumen used. Alternative technologies involving modifications to bitumen are being explored to improve pavement performance. One such approach is crumb rubber-modified bitumen, which requires experimental analysis to assess its feasibility for road pavement. This study investigates the application of Crumb Rubber Modified Bitumen (CRMB) in asphalt concrete mixes as a solution to environmental issues caused by waste tires. The experimental tests were conducted to compare the properties of CRMB with conventional VG30 bitumen. CRMB was prepared by blending VG30 bitumen with crumb rubber (CR) at varying percentages (6%, 8%, 10%, 12%, and 14%). The results indicated that 8% CR provided the best performance, increasing Marshall stability by 17.16% and reducing bitumen content by 15.66%. This study highlights the potential of CRMB in enhancing pavement stability while addressing environmental concerns related to waste tires.